2017
DOI: 10.1128/mbio.01034-17
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Distribution of the Pseudomonas Quinolone Signal Modulates Outer Membrane Vesicle Production in Pseudomonas aeruginosa

Abstract: The Pseudomonas quinolone signal (PQS) is an important quorum-sensing molecule in Pseudomonas aeruginosa that also mediates its own packaging and transport by stimulating outer membrane vesicle (OMV) formation. Because OMVs have been implicated in many virulence-associated behaviors, it is critical that we understand how they are formed. Our group proposed the bilayer-couple model for OMV biogenesis, where PQS intercalates into the outer membrane, causing expansion of the outer leaflet and consequently inducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 59 publications
(74 reference statements)
5
110
0
1
Order By: Relevance
“…This long-range stress response complements the short-range kin lysis stress system previously reported in P. aeruginosa (54). PQS activates heightened stress responses in P. aeruginosa, including the formation of outer membrane vesicles, which interfere with cytokine production and deliver toxins to target host cells (55)(56)(57). Through activation of the PqsR receptor, PQS also induces pqsE expression, which synthesizes a QS molecule that activates RhlR and is thereby responsible for regulation of key virulence factors that kill plants and animals, including hydrogen cyanide and elastase (41,58,59).…”
Section: Discussionsupporting
confidence: 69%
“…This long-range stress response complements the short-range kin lysis stress system previously reported in P. aeruginosa (54). PQS activates heightened stress responses in P. aeruginosa, including the formation of outer membrane vesicles, which interfere with cytokine production and deliver toxins to target host cells (55)(56)(57). Through activation of the PqsR receptor, PQS also induces pqsE expression, which synthesizes a QS molecule that activates RhlR and is thereby responsible for regulation of key virulence factors that kill plants and animals, including hydrogen cyanide and elastase (41,58,59).…”
Section: Discussionsupporting
confidence: 69%
“…In P. aeruginosa, the PQS molecule and associated regulatory pathway are linked to numerous cellular processes including swarm repression, stress response, cell lysis, DNA release, outer membrane vesicles (OMV) biogenesis, and biofilm development (20)(21)(22)24,29,45). The AQNOs, HQNO and NQNO, are both effective antiStaphylococcal molecules that modulate the interaction between P. aeruginosa and Staphylococcus aureus (18,25).…”
Section: Discussionmentioning
confidence: 99%
“…In the Pseudomonas literature, AQs are generally presented to contain 7-Carbon (C7) side chains (HHQ, PQS, and HQNO), yet 9-Carbon (C9; NHQ, C9-PQS, and NQNO) and 11-Carbon (C11; UHQ, C11-PQS, and UQNO) side chain variants of these molecules are also common (16,17). The extracellular presence of PQS in P. aeruginosa communities is attributed to packaging and transport in outer membrane vesicles (OMVs) (28,29), yet cell lysis could also contribute to their release (30).…”
Section: Introductionmentioning
confidence: 99%
“…The overall amphiphilicity of PQS and its task-specific functional groups enable a strong association with LPS in the outer leaflet (13). The insertion of PQS into the membrane leads to an asymmetric expansion of the outer leaflet compared with the inner leaflet, which drives the induction of membrane curvature and subsequent pinch-off of the OMV (11,14). Recent experiments have shown that other gammaproteobacteria also respond to PQS by increasing OMV formation, which suggests that small molecule-induced OMV biogenesis is a general mechanism that is driven by biophysical interactions with target membranes (15).…”
mentioning
confidence: 99%